Blood Brothers in Despair: Greek Brigands, Albanian Rebels and the Greek-Ottoman Frontier, 1829‑1831 - Basil C. Gounaris (Cahiers Balkaniques)
In the last stage of the disastrous war for Greek independence (1829‑31), the suggested northern frontier line changed three times. The uncertain future of the region, the pressure of the central government to create regular armed forces and to safeguard security along the new border land brought the local Greek and Albanian military élites, after ten years of heavy fighting, in an awkward position. Their options were restricted and their welfare as mercenaries was threatened. The crumbling Empire and the soon‑to‑be Greek nation-state, were unpredictable in their responses either as allies or as enemies. Their choices of reaction varied, yet their method was uniform: to bargain tough before compromising, even if the given choice involved mutiny and extensive civil strife. Their opponents, on the other side, Governor Ioannis Kapodistrias and Grand Vizier Mehmed Reşid had to show in the eyes of the Great Powers determination and improvisation, in order to gain the necessary prestige and win back the disputed territories. Eventually the making of the frontier forced both warlords and politicians to transform their tactics and reconsider their alliances.